MORPHOLOGICAL CHARACTERISTICS OF TISSUE MICROREGION OF THE THYROID GLAND AT EXPERIMENTAL HYPOTHYROIDISM - O. V. Gorchakova; V. N. Gorchakov; G. A. Demchenko; S. N. Abdreshov (Сибирский научный медицинский журнал)
Research purpose was to study the structures of the tissue microregion of the thyroid gland at an experimental hypothyroidism. Material and methods. The hypothyroidism model was created by mercazolilum intake at a dose of 5 mg/100 g of body mass for a month. The structure of tissue area (follicle, thyrocyte, interfollicular space) with morphometry and calculation of the integral indicators of the thyroid gland functional activity have been investigated by the light-optical and ultrastructural methods. Results and discussion. The morphophysiological structure of the thyroid gland is a tissue microregion. It unites a group of follicles and interfollicular space. The structure of the tissue miroregion have features of structural response to merkazolilum intake. The thyrostatic remedy changes the follicular organization of the thyroid gland to the predominance of small and medium follicles with signs of alteration. Thyrocytes have expansion and deformation of the granular endoplasmic reticulum cisterns, formation of intracellular colloid, reduction in the number of lysosomes and mitochondrions with their disorganization. The ratio of the area of the follicular epithelium, colloid and stroma changes at hypothyroidism. The portion of interstitial increases, there is an accumulation of tissue fluid because of weakening of a lymphatic drainage. Blood and lymphatic microvessels react by reducing the volume density to mercazolilum intake. Conclusion. The merkazolilum thyreostatics effects on morphology and metabolic and transport processes in tissue microregion. It testifies to decrease of thyroid function and the creation of hypothyroidism adequate model.